قضايا الخلاف النحوي وتطبيقاتها في القرآن الكريم : دراسة وصفية تحليلية - مرتضى، يحيى توين
This study examines the disagreements and negativity towards variation in syntax among the mainstream schools of Arabic grammar, especially in the analysis of Qur'anic text. It also examines the extent of previous scholarly studies on the subject. The study treats the historical, controversial and scholarly aspects of the evolution of grammatical variation. This research briefly cites some influences of grammatical variation on Islamic legal rulings. The research goes in line with the opinion of those who view grammatical differences and variations as beneficial to the Qur'anic textual analysis. Differences and variations simplify and expedite the comprehension of Qur'anic verses. This study also addresses the role of grammatical variation in the development of the Arabic language and syntatical analysis of Qur'anic texts. This is done by investigating the causes of conspicuous variations in plurality using the descriptive and analytical methods, with reference to the views of grammarians. The introductory chapter reviews controversial differences in all types of knowledge, focusing on variation. The analytical framework relies on theories of classical Arabic grammar and textual linguistics. The chapter on research findings discusses the positive impacts of grammatical difference and variation. Another chapter reveals the similarities between classical Arabic grammar and textual linguistics, by referring to the works of ancient Arabic linguists, namely Abdul Qahir al-Jurjani on the theory of composition as the standard of cohesion; Al-Jahiz on the term Al-Qiran (coherence) and the theory of situational consideration, which is a standard in textual linguistics. A chapter provides the textual analysis showing Arabic grammatical variation. This study concludes that variation is a positive linguistic activity that evolved from ancient times among various schools of Arabic grammar and linguists. The combination of classical Arabic grammar and textual grammar is possible on the condition that the classical heritage is preserved. The research also finds that differences in grammatical rules usually result from differences in understanding of grammatical analysis. Finally the research discusses the possibilities of grammatical differences in creating intellectual domains, conceptual development, legal deduction, and creative work, before delving into suggestions on some controversial issues in Arabic grammar.